Multisensory contributions to the 3-D representation of visuotactile peripersonal space in humans: evidence from the crossmodal congruency task. - Spence, C; Pavani, F; Maravita, A; Holmes, N (2004)
In order to determine precisely the location of a tactile stimulus presented to the hand it is necessary to know not only which part of the body has been stimulated, but also where that part of the body lies in space. This involves the multisensory integration of visual, tactile, proprioceptive, and even auditory cues regarding limb position. In recent years, researchers have become increasingly interested in the question of how these various sensory cues are weighted and integrated in order to enable people to localize tactile stimuli, as well as to give rise to the 'felt' position of our limbs, and ultimately the multisensory representation of 3-D peripersonal space. We highlight recent research on this topic using the crossmodal congruency task, in which participants make speeded elevation discrimination responses to vibrotactile targets presented to the thumb or index finger, while simultaneously trying to ignore irrelevant visual distractors presented from either the same (i.e., congruent) or a different (i.e., incongruent) elevation. Crossmodal congruency effects (calculated as performance on incongruent-congruent trials) are greatest when visual and vibrotactile stimuli are presented from the same azimuthal location, thus providing an index of common position across different sensory modalities. The crossmodal congruency task has been used to investigate a number of questions related to the representation of space in both normal participants and brain-damaged patients. In this review, we detail the major findings from this research, and highlight areas of convergence with other cognitive neuroscience disciplines.